2021
DOI: 10.1155/2021/1436088
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Value of FTO Combined with CEA or CYFRA21-1 in Nonsmall Cell Lung Cancer

Abstract: Objective. To explore the diagnostic value of FTO combined with CEA or CYFRA21-1 for nonsmall cell lung cancer (NSCLC) and to provide a theoretical basis for molecular diagnosis of NSCLC. Methods. Totally, 60 patients with nonsmall cell lung cancer (NSCLC) treated in our hospital between Feb. 2018 and Feb. 2019 were enrolled into the patient group (Pat group) and 50 healthy individuals with normal physical examination results in our hospital over the same time span into the control group (Con group). Serum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[ 17 20 ] Several studies have demonstrated the potential of FTO as a diagnostic and prognostic biomarker in lung cancer and gastric cancer. [ 19 , 21 ] Moreover, previous investigations by Xu et al [ 22 ] and Niu et al [ 23 ] have suggested that FTO plays a role in BC progression and may hold promise as a diagnostic marker for BC. In this study, we observed an increased expression of serum FTO levels was observed in BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 20 ] Several studies have demonstrated the potential of FTO as a diagnostic and prognostic biomarker in lung cancer and gastric cancer. [ 19 , 21 ] Moreover, previous investigations by Xu et al [ 22 ] and Niu et al [ 23 ] have suggested that FTO plays a role in BC progression and may hold promise as a diagnostic marker for BC. In this study, we observed an increased expression of serum FTO levels was observed in BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%